2011
DOI: 10.1016/j.neuron.2011.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The Expanding Social Network of Ionotropic Glutamate Receptors: TARPs and Other Transmembrane Auxiliary Subunits

Abstract: Ionotropic glutamate receptors (iGluRs) underlie rapid, excitatory synaptic signaling throughout the CNS. After years of intense research, our picture of iGluRs has evolved from imagining them companionless in the postsynaptic membrane to being the hub of dynamic supramolecular signaling complexes, interacting with an ever-expanding litany of other proteins that regulate their trafficking, scaffolding, stability, signaling and turnover. In particular, the discovery that transmembrane AMPA receptor regulatory p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
428
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(434 citation statements)
references
References 203 publications
(378 reference statements)
6
428
0
Order By: Relevance
“…The discovery of multiple auxiliary subunits with overlapping roles has greatly extended our understanding of the diversity of AMPAR macromolecular complexes (reviewed in 32, 108,109 . Currently identified AMPAR auxiliary subunits include TARPs, suppressor of lurcher (SOL) 110 , Cornichon homologues (CNIHs) 111 , synapse differentiation-induced genes (SynDIG I and SynDIG4) 112,113 , cysteine-knot AMPAR modulating protein family 114,115 , and germ cell-specific gene 1-like (GSG1L) protein 116 .…”
Section: Ampar Auxiliary Subunitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of multiple auxiliary subunits with overlapping roles has greatly extended our understanding of the diversity of AMPAR macromolecular complexes (reviewed in 32, 108,109 . Currently identified AMPAR auxiliary subunits include TARPs, suppressor of lurcher (SOL) 110 , Cornichon homologues (CNIHs) 111 , synapse differentiation-induced genes (SynDIG I and SynDIG4) 112,113 , cysteine-knot AMPAR modulating protein family 114,115 , and germ cell-specific gene 1-like (GSG1L) protein 116 .…”
Section: Ampar Auxiliary Subunitsmentioning
confidence: 99%
“…Of these the prototypical TARP family of AMPAR auxiliary subunits are by far the best characterized. There are seven TARPs, γ2 to γ8 (for review see 108 ). A large body of work has demonstrated that Stargazin, and other Type I TARPs (γ3, γ4 and γ8), can promote synaptic trapping of AMPARs through binding to PSD95 and, as discussed above, this interaction offers an attractive mechanism for how AMPARs are recruited and accumulated at the postsynapse during LTP 33, 98 .…”
Section: Ampar Auxiliary Subunitsmentioning
confidence: 99%
“…AMPARs are modulated by auxiliary subunits in the brain, including TARPs, cornichons, GSG1L, SynDIG1, CKAMP44, and other proteins (23)(24)(25)(26)(27)(28). Among them, TARPs are reported to affect AMPAR synthesis, maturation, trafficking, and function (29). To investigate whether TARPs participate in determining the stoichiometry and assembly of heteromeric AMPARs, we cotransfected TARP γ-2 with GluA1 and GluA2 mutants.…”
Section: Glua1 and Glua2 Have Preferred Positions In Tetrameric Assemmentioning
confidence: 99%
“…Cerebellar granule neurons (CGNs), which express high levels of stargazin, were found to lack surface AMPA-type glutamate receptors (AMPARs) in the stg mouse (3,4). Stargazin not only controls the trafficking of AMPARs, but also controls AMPAR gating (5)(6)(7)(8)(9)(10), indicating that it satisfies all of the criteria of auxiliary subunits. Stargazin is a member of a family of proteins referred to as transmembrane AMPAR regulatory proteins (TARPs) and consists of the following members: canonical type I TARPs (γ-2, γ-3, γ-4, and γ-8) and atypical type II TARPs (γ-5 and γ-7), which differ in their amino acid sequence and uniquely regulate AMPAR trafficking, gating, and neuropharmacology (7).…”
mentioning
confidence: 99%